Agricultural Collage - Jamous, Sarah (My University, 2019)
Location: nassareyah Project: agricultural collage Area: 80,000 m2 Project year: 2018-2019 Functions: Collage laborites Production center Concept Providing an environment for the student to support -and encourage the idea of agriculture By providing faculty and services with laboratories and production center Building an agriculture college protects the region -- The student graduates with high efficiency work -- Improving the image of agriculture and farmers-- Improve agricultural production-- Special Technical Education Preparing qualified graduates able to contribute effectively to thefuture Agricultural training System Raising the quality and efficiency of academic programs Research: Laborites Presence of laboratory buildings Create a seed bank Production center: Increasing food security Poverty reduction through job creation Increasing farmers ' incomes Improving agricultural land productivity